Activating change leadership practices among public school principals in the Sultanate of Oman considering the model of John Kotter - Al-Jabri, Sanad; Salah El-Din, Nesreen; Lashin , Mohammed (Al-Adab Journal, 2025)
This study aimed to find out the degree of change in leadership practice among public school principals in Oman considering the model of John Cotter. It also aimed to reveal statistically significant differences between the responses of sample about these practices attributed to gender variables, job title and come up with proposed measures to activate change leadership practices in public schools in the Sultanate of Oman.To achieve the aims of the study, the descriptive method was used, and a questionnaire consisting of (38) paragraphs was prepared, including the questionnaire on eight stages of the John Cotter model of Change Leadership. The tool was applied to a sample of (456) teachers in the governorate of North Al Batinah. The study reached several results including the following:- The responses of the study sample members to the degree of change leadership practice among public school principals in Oman came considering the model of John Cotter to a very high degree.- There are no statistically significant differences in teachers ' estimates in the degree of change leadership practice among public school principals in the Sultanate of Oman considering the John Cotter model at the significance level (α ≤ 0.05) attributed to gender variables and job title.The study came up with a set of suggestions that will contribute to activating the change leadership practitioner in public schools in the Sultanate of Oman.